Exploring the burden of short-term CHOP chemotherapy adverse events in post-transplant lymphoproliferative disease: a comprehensive literature review in lymphoma patients. Issue 1 (15th December 2021) - Watson, Crystal; Barlev, Arie; Worrall, Jodie; Duff, Steve; Beckerman, Rachel
Abstract: Purpose: Cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP) is a treatment for post-transplant lymphoproliferative disease (PTLD) following solid organ transplant (SOT) after failing rituximab, an aggressive and potentially fatal lymphoma. This study explores the humanistic and economic burden of CHOP-associated adverse events (AEs) in PTLD patients. Since PTLD is rare, searches included lymphoproliferative disease with lymphoma patients. Design: This comprehensive literature review used the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) protocol, pre-specifying the search strategy and criteria. CHOP-associated short-term AEs with an incidence of >4% were sourced from published literature and cancer websites to inform the search strategy. PubMed and EMBASE searches were used to identify humanistic and economic burden studies. Results: PubMed and EMBASE searches identified 3946 citations with 27 lymphoma studies included. Studies were methodologically heterogeneous. Febrile neutropenia (FN) was the AE most encountered, followed by chemotherapy-induced (CI) anemia (A), infection, CI-nausea and vomiting, thrombocytopenia, and CI-peripheral neuropathy (PN). FN and infections were associated with significant disutility, increased hospitalization, and extended length of stay (LOS). Infections and CIPN significantly impacted the utility of patients and CIA-related fatigue showed reductions in quality of life (QoL). Many patients continue to have QoL deficits continued even after AEs were treated. Management costs varied greatly, ranging from nominal (CIPN) to over $100, 000 in the USA for infections, EUR 10, 290 in Europe for infections, or CAN$1012 in Canada for FN. Cost of outpatient care varied but had a lower economic impact compared to hospitalizations. Conclusions: Short-term AEs from CHOP in the lymphoma population were associated with substantial humanistic and economic burden.